Induction of Semi-Dwarf Trait to a Three Pistil Tall Mutant Through Breeding With Increased Grain Numbers in Wheat - Irshad, Ahsan; Guo, Huijun; Ur Rehman, Shoaib; Gu, Jiayu; Ahmed, Rana Imtiaz; Hussain, Manzoor; Ammar, Ali; Ali, Imtiaz; Zafar, Akash; Wang, Chaojie; Zhou, Chunyun; Qiu, Lin; et al. (Frontiers in Genetics, 2022)
Multi-ovary wheat is a unique germplasm with more grains per spike and promising potential for the seed production of hybrid wheat. The purpose of present study was to transfer multi-ovary trait in semi dwarf plant for increase production of grains in wheat crop. Therefore, tall, semi dwarf and dwarf plants were crossed with plants containing three pistilled trait. Three pistil tall plant was used as female parent. While tall (Synthetic hexaploid), semi dwarf and dwarf plants were used as male parents. F1 and F2 progenies with parents were planted during 2015-16 by using RCBD. The outcome of crosses showed that multiovary tall gave significant difference for all four traits (days to maturity, number of seeds per spike, grain weight per spike and plant height) in both generations. Maximum number of grains/spike were obtained from the cross three pistilled tall versus dwarf parent (P1/P6) in F1 and F2 generations. The cross also resulted in significant reduction in height (96 cm). Further heterosis studies conducted with crosses between three pistil tall versus dwarf parent (P1/P6) showed maximum heterosis (60.0) for number of grains/spike and heterobeltosis (26.19). In case of grain weight per spike, heterosis value was also positive and significant (17.7). While, for other traits, their values were negative for heterosis and heterobeltosis. High number of grains and grain weight were found to be associated with positive heterobeltosis but plant height and maturity had negative affirmation with heterobeltosis. Heterosis study also indicated dominant generation for three-pistil trait. Thus, the study clearly signified that grain yield can be increased by using multi-ovary genotype having semi dwarf height. This new germplasm will be helpful for breeder to increased production of wheat crop in southern climate of Pakistan.